PROFIL KOMUNITAS FOTOGRAFI PEKANBARU (KFP) - Siti Fatonah; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The photography community is a social group that occurs in modern society. In this case we need to know the profile of photography community, photography community activity and photographer style towards determining object. This type of research is descriptive qualitative research. Qualitative research is a study that intends to understand the phenomenon of what is experienced by research subjects such as behavior, motovation, actions and others holistically and with descriptions in the form of words and language, as well as will be done by the author that is describing or making a description of the subject about the activities and style of photography art in the city of Pekanbaru, where the number of informants amounted to 6 people. From the results of the research Pekanbaru Photography Community (KFP) has activities or activities that are fositive to them and the environment. Pekanbaru Photography Community Activity (KFP) is more oriented towards togetherness, sharing knowledge and hospitality. Photographic community activity is displayed through its activities, such as regular meetings, hunting, exhibitions, seminars and workshops, and social activities. In the style of the photographer to the individual object has a tendency of each, in addition to all items there also like young women, landscape (nature), human, miniature and product. Keywords: community, activity, style